The nutritional health beliefs of nurses in Japan, Thailand, China and Australia - Sue Turale (2020)
© 2020, Thailand Nursing and Midwifery Council. All rights reserved. Nurses’ beliefs about food and nutrition influence the care and advice they give patients, their families, nurses and others, but these beliefs have not been extensively researched before. This paper presents findings from the qualitative phase of a large q-methodology study that involved both quantitative and qualitative methods. The phase of the study reported here utilized a qualitative descriptive approach regarding a range of beliefs, and in-depth interviews with 240 participants who comprised 30 academics and 30 clinical nurses each from China, Thailand, Japan and Australia. Content analysis was employed to analyse the extracted data regarding their beliefs about nutrition and nutritional supplements, and the sources of these beliefs. Findings and resultant discussion are reported about 17 specific nutritional beliefs. We concluded that many nurses in all the surveyed countries had some false and scientifically unsupported beliefs about nutrition, derived primarily from the media or personal experience. Study findings speak to the need for nurses to critically examine the sources of information they use in their practice and teaching, as well as a need for research to be reported responsibly and accurately. The review of the presented evidence about nutrition will assist nurses in their clinical and teaching practice, and hopefully inspire them to use evidence-based practice in future.